Effectiveness of 1% Versus 0.2% Chlorhexidine Gels in Reducing Alveolar Osteitis from Mandibular Third Molar Surgery: A Randomized, Double-Blind Clinical Trial (Medical Forum Monthly, 2024)
Objective: One of the leading, recurrent and most familiar problem after extraction is alveolar osteitis (AO) .This case was designed to compare and publish the effectiveness of chlorhexidine (CHX) gel in concentrations 1% and .2% in combating post-operative complication of AO especially after surgical removal of retained mandibular molars .Moreover , this study also aimed at assessment and analysis of quality of treatment after use of CHX gel on oral wellness. Study Design: Observational Study Place and Duration: This study was conducted at the department of Oral Medicine, Avicenna Dental College Lahore. from January 2017 to 2019. Material Methods: This case study was done on basis of practical clinical practice and on patients. The study was randomized. Total patients subjected to treatment were eighty eight. All the patients after post extraction were treated with CHX gel to overcome complication AO in concentration either 1% or .5%. About 41 patents were treated with 1% of CHX gel and 47 remaining were treated with .2% of gel after extraction. The instructions were given to patients to apply this gel twice a day for duration of one week at least. After a week, assessment was made regarding CHX gel application outcomes. Results: With the assessment and careful observation, it was found that about 13% patient suffered from AO after application of CHX gel in concentration of 0.2% and about 7% patients suffered from AO after application of CHX gel in concentration of 1%. Such difference was not so important with respect to statists. The pain and inflammation that patients suffered post surgically was almost same during whole one week duration Conclusion: In a nutshell, there is no significant difference post surgically found in patients after application of CHX gel either in concentration 1% or .2% in case of extraction of retained mandibular third molar.